Ninth building - Zou, Jingzhi 1952- (Open Letter Press, 2023)
Ninth Building is a fascinating collection of vignettes drawn from Zou Jingzhi's experience growing up during the Cultural Revolution, first as a boy in Beijing and then as a teenager exiled to the countryside. Zou poetically captures a side of the Cultural Revolution that is less talked about--the sheer tedium and waste of young life, as well as the gallows humor that accompanies such desperate situations
"Originally published in Chinese as Jiu dong by Fa lü chu ban she"--Title page verso
Keywords: Jugend; Kulturrevolution -- China; Teenagers / Fiction; Beijing (China) / Fiction; Beijing (China) / Social conditions / 20th century / Fiction; China / History / Cultural Revolution, 1966-1976 / Fiction; Bildungsromans, Chinese; Poetry; Zou, Jingzhi / Translations into English; Bildungsromans; Biographical fiction; Fiktionale Darstellung